Successful delivery of docetaxel to rat brain using experimentally developed nanoliposome: a treatment strategy for brain tumor - Tapan Kumar Shaw; Dipika Mandal; Goutam Dey; Murari Mohan Pal; Paramita Paul; Samrat Chakraborty; Kazi Asraf Ali; Biswajit Mukherjee; Amal Kumar Bandyopadhyay; Mahitosh Mandal (Taylor & Francis Group, 2017)
Docetaxel (DTX) is found to be very effective against glioma cell in vitro. However, in vivo passage of DTX through BBB is extremely difficult due to the physicochemical and pharmacological characteristics of the drug. No existing formulation is successful in this aspect. Hence, in this study, effort was made to send DTX through blood-brain barrier (BBB) to brain to treat diseases such as solid tumor of brain (glioma) by developing DTX-loaded nanoliposomes. Primarily drug-excipients interaction was evaluated by FTIR spectroscopy. The DTX-loaded nanoliposomes (L-DTX) were prepared by lipid layer hydration technique and characterized physicochemically. In vitro cellular uptake in C6 glioma cells was investigated. FTIR data show that the selected drug and excipients were chemically compatible. The unilamellar vesicle size was less than 50 nm with smooth surface. Drug released slowly from L-DTX in vitro in a sustained manner. The pharmacokinetic data shows more extended action of DTX from L-DTX in experimental rats than the free-drug and Taxotere®. DTX from L-DTX enhanced 100% drug concentration in brain as compared with Taxotere® in 4 h. Thus, nanoliposomes as vehicle may be an encouraging strategy to treat glioma with DTX.